Design and the Social: Intersections between design, critique and STS - Danholt, Peter; Halse, Joachim (STS Encounters, 2016)
From the introduction: The notion of society provided by the French philosopher Gabriel Tarde challenges the idea that society - or rather societies - are exclusively human. Rather, societies are all around, above, below, besides and inside of the human and on a scale ranging from the minuscule to the interstellar, arguably. Such a definition of society is fascinating, since taken for granted notions of society and the social that implicitly rely on society as being exclusively human, become in return destabilized. We are invited to think, study and act the social and society differently. This special issue constitutes an attempt at such an invitation.